Kegiatan Supervisi Kepala Sekolah dengan Teknik Group Discussions untuk Meningkatkan Kemampuan Guru dalam Menyusun Soal Tes Hasil Belajar Di SDN Penjaringansari II No. 608 Surabaya - Pratiwi, Nunuk Sri Wahyu (Universitas Nusantara PGRI Kediri, 2021)
This school action research is based on the results of the supervision carried out by the principal on the ability of the teachers at SDN Penjaringansari II No. 608 Surabaya, shows that often teachers in compiling questions are still guided by the LKS. This means that the teachers arrange questions by taking all or part of the questions in the LKS. In addition, teachers also use tests that have existed in previous years and are then adjusted to the teaching materials. On the other hand, most of the teachers have not been able to arrange tests, so they often look for several sets of questions that already exist. This study aims to determine the improvement of teachers' ability in preparing learning outcomes test questions through Principal Supervision activities with group discussions techniques at Penjaringansari II Public Elementary School No. 608 Surabaya in the odd semester of the 2016-2017 school year. Methods of data collection using the method of documentation and observation. The result of this research is that the Principal's Supervision activities with group discussions technique can improve the ability of teachers in preparing learning outcomes test questions at Penjaringansari II Public Elementary School No. 608 Surabaya in the odd semester of the 2016-2017 school year. This can be proven from the results of observations which show that in the first cycle the percentage of teachers' ability in compiling learning outcomes test questions was 75.6% in the sufficient category, then increased in the second cycle by 91.1% in the very good category. In addition, the principal's supervision activities with the group discussions technique showed the readiness of teachers to participate in the activities in the first cycle, the average percentage was 79.7% in the good category and increased in the second cycle by 97% in the very good category.